Competition, markups, and gains from trade: A quantitative analysis of China between 1995 and 2004 - HSU, Wen-Tai (Institutional Knowledge at Singapore Management University, 2019)
This paper provides a quantitative analysis of gains from trade in a model with head-to-head competition using Chinese firm-level data from Economic Censuses in 1995 and 2004. We find a significant reduction in trade cost during this period, and total gains from such improved openness during this period is 7:1%. The gains are decomposed into a Ricardian component and two pro-competitive ones. The procompetitive effects account for 20% of the total gains. Moreover, the total gains from trade are 13 31% larger than what would result from the formula provided by ACR (Arkolakis, Costinot, and Rodríguez-Clare 2012), which nests a class of important trade models, but without pro-competitive effects. We find that head-to-head competition is the key reason behind the larger gains, as trade flows do not reflect all of the effects via markups in an event of trade liberalization. One methodological advantage of this paper’s quantitative framework is that its application is not constrained by industrial or product classifications; thus it can be applied to countries of any size.